2018
DOI: 10.1371/journal.pntd.0006603
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of cases of severe fever with thrombocytopenia syndrome bunyavirus infection in China, 1996: A retrospective serological study

Abstract: BackgroundA cluster of eleven patients, including eight family members and three healthcare workers with fever and thrombocytopenia occurred in Yixing County, Jiangsu Province, China, from October to November 1996. However, the initial investigation failed to identify its etiology. Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease caused by SFTS bunyavirus (SFTSV), which was first discovered in 2009. The discovery of novel SFTSV resulted in our consideration to test SFTSV on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Severe fever with thrombocytopenia syndrome (SFTS) is an emerging hemorrhagic fever caused by the severe fever with thrombocytopenia syndrome virus (SFTSV), which is classified in the order Bunyavirales, family Phenuiviridae, and genus Phlebovirus [1][2][3]. SFTS was first confirmed among rural areas in China in 2009 and subsequently reported in North Korea in 2009, South Korea in 2012 and Japan in 2013 [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Severe fever with thrombocytopenia syndrome (SFTS) is an emerging hemorrhagic fever caused by the severe fever with thrombocytopenia syndrome virus (SFTSV), which is classified in the order Bunyavirales, family Phenuiviridae, and genus Phlebovirus [1][2][3]. SFTS was first confirmed among rural areas in China in 2009 and subsequently reported in North Korea in 2009, South Korea in 2012 and Japan in 2013 [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a cluster of cases of SFTS in 1996 was uncovered and reported in a new study. It has been suggested that the SFTSV has been circulating in China for more than 10 years prior to 2009 [2]. An SFTSV-like virus called the Heartland virus was also isolated in the United States in 2012 [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Severe fever with thrombocytopenia syndrome (SFTS) was first confirmed in China in 2009, and retrospective serological studies showed that SFTSV-specific IgM and IgG were detected in the sera of patients in China in 1996 and retrospectively reported in South Korea in 2010, in Japan in 2013, and in Vietnam in 2017. [2][3][4][5][6] Most SFTSV infections occur through bites from the tick Haemaphysalis longicornis, although SFTSV transmission can also occur through close contact with an infected patient. [2][3][4][5][6][7][8][9][10][11] Scrub typhus is a bacterial disease caused by Orientia tsutsugamushi that is transmitted primarily by the bite of the Leptotrombidium spp.…”
Section: Introductionmentioning
confidence: 99%